The Relationship Between Family Caregiver Involvement in Cancer Patient Care and the Quality of Life of Cancer Patients - Wildan Azka Taslimi; Yulia Rizka; Sofiana Nurchayati (CV. Rayyan Dwi Bharata, 2025)
Cancer is a global health issue that impacts the physical, psychological, and social well-being of patients. The quality of life of cancer patients is influenced by various factors, one of which is family support. This study aims to analyze the relationship between family caregiver involvement in cancer patient care and the quality of life of cancer patients at a Regional General Hospital in Riau Province. The study uses a correlational method with a cross-sectional approach, involving 82 samples selected through purposive sampling. Data were collected using a questionnaire, and univariate analysis showed that the majority of respondents were aged 41-60 years (67.1%), female (73.2%), had a last education of elementary school (32.9%), worked as housewives (35.4%), had a monthly income of less than IDR 3,200,000 (76.8%), and the majority had breast cancer at stage III (67.1%). The Pearson correlation test showed a p-value of 0.000 (< 0.05) and r-count 0.611 (> r-table 0.214), indicating a significant relationship between family caregiver involvement and cancer patients' quality of life. The higher the involvement of family caregivers in cancer patient care, the better the quality of life of the patients.